Die Finanzkrise 2008/2009 und die Aktualität der gesamtwirtschaftlichen Finanzierungsrechnung - Reimund Mink; Klaus-Dieter Voy (Wirtschaftsdienst, 2017)
Finanzkrisen hatten immer beträchtliche wirtschaftliche Einbußen und hohe soziale Kosten zur Folge. So war es bei der Weltwirtschaftskrise 1929, aber auch bei der jüngsten Finanzkrise 2008/2009. Damit verbunden waren nicht nur tiefe Einschnitte für die Finanz- und die Realwirtschaft, sie entfachten auch Diskussionen über die theoretische Behandlung des Verhältnisses beider Teilbereiche und die adäquate statistische Erfassung und Darstellung finanzieller Transaktionen in gesamtwirtschaftlichen Zusammenhängen. – – The paper describes the reasons why macroeconomic sectoral financial accounts (SFA) are gaining importance in current discussions of economic. This was not always the case: after a promising start and gradual expansion in the 1960s, the SFA lost political impact. The main reason for that was the transition from credit to money supply policy in the 1970s. However, the financial crisis of 2008/2009 led to a re discovery of the financial sphere, which was accompanied by the revision of the System of National Accounts in 2008. Its focus in terms of financial issues was three fold: a deeper subdivision of the financial sector, a refined breakdown of the financial instruments, and the presentation of sectoral links by 'from whom to whom' relationships. The intensive cooperation between international organisations, central banks and statistical offices in the area of economic statistics and national accounts, as well as the legal requirements at the European level to provide harmonised data, supported its rapid implementation afterwards. This was also driven by the design and use of securities and credit databases.
Keywords: E01; E44; G20; 330